Analisis Kemampuan Komunikasi Matematis Siswa Kelas X pada Materi Eksponen dan Logaritma - Fatimatus Solihah; Saiful Fadli; Lalu Ajimudiardi Akbar; Helmi Rahmawati; Nurlaela Safriani (MAN 4 Kota Pekanbaru, 2026)
The problem in this study is that students’ mathematical communication skills are still not optimal, particularly in representing mathematical ideas, using mathematical symbols and notations appropriately, and explaining problem-solving procedures systematically. This study employed a descriptive qualitative approach involving 16 tenth-grade students. Data were collected through written tests, observations, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing. The results showed that students’ mathematical communication skills were at a moderate level. Of the 16 students, 3 students (16.75%) were categorized as high, 10 students (62.5%) as moderate, and 3 students (20.75%) as low. High-category students were able to communicate ideas systematically and explain procedures clearly, while moderate and low-category students still faced difficulties in representation, notation use, and procedural explanation. Thus, mathematical communication skills in exponents and logarithms need further improvement.